СОЦІАЛЬНО-ФІЛОСОФСЬКІ ВИМІРИ НАУКИ: ІСТОРИЧНИЙ РОЗВИТОК СОЦІАЛІЗАЦІЇ НАУКИ ТА СУЧАСНІ ПАРАМЕТРИ НАУКОВОЇ ПРОФЕСІЇ - Гейко, С. М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Здійснено філософський аналіз процесу соціалізації науки як результату історичного розвитку. Аналізуються соціальні параметри наукової професії, зокрема, сучасні соціологічні дослідження науки дозволили виділити чотири соціальні риси наукової професії. Гейко С.Н. Социально-философское измерение науки: историческое развитие социализации науки и современные параметры научной профессии. Осуществлен философский анализ процесса со- циализации науки как результата исторического развития. Анализируются социальные параметры на- учной профессии, в частности, современные социологические исследования науки позволили выделить четыре основные социальные черты научной профессии. Ключевые слова: наука, научное сообщество, научное знание, научное признание S. Geiko. The Social Philosophical Dimensions of Science: Historical Development of Science Socialization and Modern Parameters of Scientific Profession. The science as social institution is a form of social conscience connected to production of scientific theoretical knowledge. It is a special system of interrelations between scientific organizations and members of scientific community, an environment of scientific periodic press functioning and scientific conferences and discussions holding, the system of norms and values, and finally it represents the connection of science to other social institutions (politics, social movements, business etc). It is characterized by next set features. The philosophical analysis of science socialization process as result of historical development is undertaken. The social parameters of scientific profession are analyzed. In particular, modern sociological researches of science allowed selecting four basic social features of scientific profession. The first of them is ownership of special system of scientific knowledge, for preservation and widespread of which scientists are responsible. The second feature is autonomy of scientific profession for incorporation and training of new members and control of their professional behavior. The third feature is presence of different forms of reward inside scientific profession which are sufficient stimuli for specialists guarantying their high motivation for scientific career. The fourth feature is interest of social environment in products of labor of scientific community members, which ensures science existence and activity. All these features are important for science and scientific profession. Key words: science, scientific community, scientific knowledge, scientific status recognition.